Influence Family Support and Level of Compliance in Taking Medication to Quality of Life for People with HIV/AIDS at the Sehat Peduli Kasih Foundation Semarang City - Patmawati; Bagoes Widjanarko; Mateus Sakundarno Adi (Jurnal Penelitian Pendidikan IPA, 2025)
HIV is a global health problem and a social challenge for sufferers. Indonesia is the country with the 14th highest estimated ODHIV in the world with a total of around 570,000 people, Indonesia is also ranked 9th in terms of new cases of HIV infection which reached 28,000 cases in 2023. The severity of the problems faced by ODHA can affect their quality of life, therefore patients with HIV/AIDS need support and encouragement from family, peers, and health workers to be able to improve their health. This research aims to analyze the influence of family support and drug compliance levels on the quality of life of people with HIV/AIDS (ODHA) at the Sehat Peduli Kasih Foundation of Semarang City. This research uses a cross-sectional study design. The case population is all patients who are diagnosed with HIV/AIDS and receive assistance from the Semarang City Sehat Peduli Kasih Foundation, the affordable population is all patients aged 20-49 years and receive ARV therapy. The sampling technique in this study uses the purposive sampling method according to the criteria desired by the researcher. The total sample is 63 people. Bivariate analysis using Chi Square test and multivariate analysis using double logistic regression test. Multivariate test proved that drug compliance and family support were proven to affect the quality of life of people with HIV/AIDS with a p-value = 0.000 greater than 0.05. Further analysis shows that the drug compliance variable is the most dominant influence on the quality of life of people with HIV/AIDS with a 95% CI value of 28,000 (6,670 - 117,537). Compliance with medication, family support, marital status, and education level are proven to have an impact on the quality of life of people with HIV/AIDS at the Sehat Peduli Kasih Foundation in Semarang City.